Analisis Kesalahaan Penggunaan Kalimat Efektif dalam Novel “Dilan, Dia adalah Dilanku Tahun 1990” Karya “Pidi Baiq” - Mulyadi Bagas Wicaksono; A. Rizki Wahyu Pradana; Dewi Ayu Setianingsih; Mohamad Afrizal (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
This study aims to identify, classify, and analyze errors in the use of effective sentences in the novel Dilan: Dia adalah Dilanku Tahun 1990 by Pidi Baiq. A qualitative descriptive method was employed, with data collected through reading and note-taking techniques. The data source was the novel Dilan: Dia adalah Dilanku Tahun 1990, while data analysis involved the stages of data collection, classification, analysis, presentation, and conclusion drawing. The findings identified 15 errors related to the use of effective sentences, including word redundancy, subject repetition, excessive use of emphasis markers, ineffective sentence structures, and ambiguous expressions. Word redundancy emerged as the most dominant error, characterized by unnecessary repetition and excessive language elements that reduced sentence economy. Subject repetition and excessive emphasis markers also decreased sentence efficiency and clarity, while ineffective structures and ambiguous wording affected the precision of meaning. These findings indicate that several sentences in the novel do not fully meet the principles of effective writing, particularly regarding economy, clarity, and accuracy. However, these linguistic features also contribute to the novel’s distinctive narrative style, characterization, and communicative atmosphere. This study provides valuable insights into the application of effective sentence principles in literary works and is expected to serve as a reference for language studies, literary criticism, and editing practices.